Manufacture Technological Structure Innovation Strategy Development Modeling in Terms of the New Ecological and Economic Doctrine - Onyshchenko, Andriy; Kharchenko, Yuriy (International Journal of Engineering and Technology, 2018)
Economic growth with restrictions on ensuring economic balance implementation and greenhouse gases balance with the efficiency criterion in the form of production construction technological structure sustainable development model using research construction methods is fulfilled in the article. Aggregation procedure method is developed based on original micro-description research and the ecological and economic production function is constructed in explicit analytical form. Gross output modeling is carried out depending on the draw economic and ecological resources amount and technological production structure changes. The obtained results give an opportunity to evaluate any mechanism introduction impact for environmental management on the environment state and industrial enterprises economic development. Â Â